Antidiabetic Activity And Toxicity Study Of Orthosiphon Stamineus Benth Ethanolic Extracts - Mohamed, Elsnoussi Ali Hussin (2012)

(untitled)
Orthosiphon stamineus is a popular folk medicine used for the treatment of many diseases including diabetes mellitus. This study was under taken to investigate the antidiabetic activity, mechanism of actions and toxicity study of standardized O. stamineus leaves extract. Leaves of O. stamineus were extracted with 95%, 75%, 50%, and 25% (ethanol : water) v/v respectively. Only the 50% ethanolic extract (1,000 mg/kg), reduced the blood glucose level of rats loaded subcutaneously with 200 mg/kg glucose.